Síntese de espiro compostos via reações multicomponentes dominó Knoevenagel/Michael/ciclização organocatalisadas por líquidos iônicos - Westphal, Regina (2023)
Spiro compounds are organic substances formed by at least two rings connected by only one atom, called spiro-atom. These molecules are present in natural products isolated from several sources. In addition, they have a range of biological activities and, therefore, have attracted the attention of many researchers as a primary structure for the discovery of new drugs. However, the synthesis of spiro compounds is a major challenge for synthetic organic chemists, given their 3D structural properties, conformational rigidity and intrinsic complexity. In this sense, multicomponent organocatalyzed domino reactions have gained prominence in the literature for obtaining this class of compounds, given the numerous advantages of these processes, such as: generation of structurally diverse products, varied synthesis possibilities, highly convergent routes and better reaction efficiency. Furthermore, the use of ionic liquids as organocatalysts has emerged as an ecologically suitable alternative for many organic reactions. Therefore, in this work a Knoevenagel/Michael/cyclization domino multicomponent methodology, using ethanol as solvent and the ionic liquid 1- methylimidazolium chloride as catalyst was developed for the synthesis of spiro compounds. The reaction conditions considered ideal were determined from a methodological study varying solvent, catalyst, amount of catalyst, temperature, and heating mode. The generality of the methodology was evaluated by exploring the scope of the reaction, varying the starting materials (isatin, malononitrile, and barbituric acid). The synthesized spiro compounds were obtained with yields ranging from 36-98% and the X-ray structure of compound 139b, 139d and 139k were obtained. The asymmetric synthesis of compound 139a was also carried out, using chiral ionic liquids and a chiral phosphoric acid derivative as organocatalysts. However, unfortunately, low enantiomeric excess values were obtained (4-6% ee) by chiral HPLC. Finally, the in vitro antiproliferative activities of the spirocycles 139a-q against four types of human cancer cell lines including HCT116 (human colon carcinoma), PC3 (prostate carcinoma), HL60 (promyelocytic leukemia), and SNB19 (astrocytoma) were screened by MTTbased assay. It is noteworthy that spiro compound 139c inhibited the four cell lines tested with the lowest IC50 values: 52.81 µM for HCT116, 74.40 µM for PC3, 101 µM for SNB19, and 49.72 µM for HL60.